Self and Nonself - López-Larrea, Carlos (Advances in Experimental Medicine and Biology, 2012)
In 1960 Sir Frank Macfarlane Burnet received the Noble Prize in Physiology and Medicine. He titled his Nobel Lecture "Immunological Recognition of Self" emphasizing the central argument of immunological tolerance in "How does the vertebrate organism recognize self from nonself in this the immunological sense-and how did the capacity evolve." The concept of self is linked to the concept of biological self identity. All organisms, from bacteria to higher animals, possess recognition systems to defend themselves from nonself. Even in the context of the limited number of metazoan phyla that have been studied in detail, we can now describe many of the alternative mechanism of immune recognition that have emerged at varying points in phylogeny. Two different arms-the innate and adaptive immune system-have emerged at different moments in evolution, and they are conceptually different. The ultimate goals of immune biology include reconstructing the molecular networks underlying immune processes.